Empirical Analysis of the Validity and Reliability of Creative Thinking Skills Test Instruments on Static Fluid Material for High School Students - Dya Atul Fahmi; Parno Parno; Khusaini Khusaini; Marlina Ali (Kasuari: Physics Education Journal (KPEJ), 2026)
The accuracy of learning assessment results is greatly influenced by the quality and reliability of the instruments used, so instrument validation is a crucial step in measuring students' creative thinking abilities. However, many instruments have not been properly validated, potentially producing inaccurate data and biased conclusions. This study aims to analyze the validity and reliability of a creative thinking ability test instrument about static fluids for high school students using a quantitative descriptive approach. The instrument consists of eight fill-in-the-blank questions structured based on creative thinking indicators and completed independently by students. Data analysis included item validity testing, reliability testing, difficulty level analysis, and discriminatory power analysis. The results show that all items are valid, the instrument is reliable, most items are at a moderate level of difficulty, and have adequate to very high discriminatory power. Thus, this test instrument is suitable for use as a tool for assessing high school students' creative thinking abilities.